2001
DOI: 10.1038/sj.bjp.0704311
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO) modulation of PAF‐induced cardiopulmonary action: interaction between NO synthase and cyclo‐oxygenase‐2 pathways

Abstract: 1 To further investigate into the mechanisms of PAF-induced cardiopulmonary actions, we examined the eects of the nitric oxide synthase (NOS) inhibitor L-N o -nitro-L-arginine (L-NNA), of the speci®c cyclooxygenase-2 (COX-2) inhibitor NS 398, and of the combined presence of both COX and NOS inhibitors on the PAF responses in the heart lung preparation of guinea-pig (HLP). 2 In HLPs perfused with homologous blood, dose-response curves for the haemodynamic and bronchial eects of PAF (1 ± 32 ng) were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…COX-2 was constitutively expressed also in isolated guinea pig trachea (Nieri et al, 2006) and appeared to mediate the spontaneous tone in this preparation (Charette et al, 1995). Constitutively expressed COX-2 contributed also to the arachidonic acid-induced (Ermert et al, 1998a) and the PAFinduced (Fabi et al, 2001) vascular response in isolated rat lungs. COX-2 can also be induced in most cell types in the lung by a broad range of proinflammatory stimuli (Belvisi et al, 1997;Bradbury et al, 2002;Mitchell et al, 1994) Non-steroidal anti-inflammatory drugs The COX enzyme is an important pharmacological target.…”
Section: Role Of Cox-1 and Cox-2 In Biological Responsesmentioning
confidence: 97%
“…COX-2 was constitutively expressed also in isolated guinea pig trachea (Nieri et al, 2006) and appeared to mediate the spontaneous tone in this preparation (Charette et al, 1995). Constitutively expressed COX-2 contributed also to the arachidonic acid-induced (Ermert et al, 1998a) and the PAFinduced (Fabi et al, 2001) vascular response in isolated rat lungs. COX-2 can also be induced in most cell types in the lung by a broad range of proinflammatory stimuli (Belvisi et al, 1997;Bradbury et al, 2002;Mitchell et al, 1994) Non-steroidal anti-inflammatory drugs The COX enzyme is an important pharmacological target.…”
Section: Role Of Cox-1 and Cox-2 In Biological Responsesmentioning
confidence: 97%
“…Differences were considered to be significant when P < 0.05. For details see our previous studies [8,9].…”
Section: Statisticsmentioning
confidence: 99%
“…Recent studies reported that PAF stimulates nitric oxide synthase (NOS) to release nitric oxide (NO) and that PAF actions are mediated by this endogenous NO in endotoxic shock, cardiopulmonary actions, microvascular permeability, and bowel injury in animal experiments. 24–28 NO is produced by a family of NOS, including neuronal NOS (nNOS, type 1), inducible NOS (iNOS, type 2), and endothelial NOS (eNOS, type 3). All three major isoforms of NOS have been demonstrated immunohistochemically in different cells of the organ of Corti and other parts of the auditory systems of guinea pigs.…”
Section: Introductionmentioning
confidence: 99%